Respuesta :
thhe easiest way would be to solve for y first
4x=3y-7
add 7
4x+7=3y
divide both sides by 3
(4x+7)/3=y
try each
x=4
(4(4)+7)/3=y
(16+7)/3=y
(23)/3=y
7 and 2/3=y
(4,7.66666)
x=5
(4(5)+7)/3=y
(20+7)/3=y
(27)/3=y
9=y
(5,9)
x=6
(4(6)+7)/3=y
(24+7)/3=y
(31)/3=y
10 and 1/3=y
(6,10.333)
(4,7.66666)
(5,9)
(6,10.333)
when x=4, y=7 and 2/3
when x=5, y=9
when x=6, y=10 and 1/3
4x=3y-7
add 7
4x+7=3y
divide both sides by 3
(4x+7)/3=y
try each
x=4
(4(4)+7)/3=y
(16+7)/3=y
(23)/3=y
7 and 2/3=y
(4,7.66666)
x=5
(4(5)+7)/3=y
(20+7)/3=y
(27)/3=y
9=y
(5,9)
x=6
(4(6)+7)/3=y
(24+7)/3=y
(31)/3=y
10 and 1/3=y
(6,10.333)
(4,7.66666)
(5,9)
(6,10.333)
when x=4, y=7 and 2/3
when x=5, y=9
when x=6, y=10 and 1/3
Rearranging the equation gives y = (4x + 7) / 3. Directly substitute the values of x given to the equation.
A. 4 : y = ((4)(4) + 7) / 3 = 23/3
B. 5 : y = ((4)(5) + 7) / 3 = 9
C. 6 : y = ((4)(6) + 7) / 3 = 31/3
A. 4 : y = ((4)(4) + 7) / 3 = 23/3
B. 5 : y = ((4)(5) + 7) / 3 = 9
C. 6 : y = ((4)(6) + 7) / 3 = 31/3